The Perception of Female Saudi English Students of the Relative Value of Giving Feedback on Academic Writing through Conferencing - Alrezqi, Wafa’a Mueed; Althaqafi, Abeer Sultan (American Journal of Social Sciences and Humanities, 2019)
The present study focuses on feedback-based writing conferences that involve feedback sessions with the teacher in a more dialogic and collaborative atmosphere to respond to students’ writing. The rationale behind eliciting students’ views and preferences regarding one-on-one and group FBWCs stems from the importance of fostering effective collaboration between students and their teachers using the learners’ preferred approaches of critical and constructive discussions. Three research questions were developed to guide the mixed methods study, which focused on students’ perceptions, their preferences concerning individual or group FBWCs, and their suggestions for better implementation of FBWCs in foundational academic writing courses. The study’s participants were 77 first-year female students majoring in English. All the students responded to an online survey, and nine of them voluntarily participated in semi-structured interviews. Statistical analyses of quantitative data were performed by SPSS, using a descriptive analysis approach in addition to using paired t tests. A thematic analysis approach was used to analyse qualitative data. Findings revealed students’ positive views about the usefulness of FBWCs for their academic writing development. The students’ responses indicated no significant differences between their preferences for individual or group FBWCs; however, students emphasized their needs for adequate and meaningful feedback in collaborative and motivating environments.